Legalitas Persidangan Perkara Pidana Di Pengadilan Secara Elektronik - Ririn Kurniasi (Satya Dharma : Jurnal Ilmu Hukum, 2022)
The effects of the pandemic made digital technology into the courtroom. In connection with this research, the thing that wants to be studied is, firstly for the mechanism of applying event law to online trials in criminal cases in Indonesia, secondly how online trials accommodate the process of proof in criminal cases in Indonesia. The research method used in this research is to use a type of normative legal research, namely research that in its study refers to and bases on the norms and rules of law, applicable laws and regulations, legal theories and doctrines, jurisprudence, and other literature materials relevant to the research topic discussed. The result of this study is, the first mechanism for the application of event law in online trials in criminal cases as stipulated in Supreme Court Regulation No. 4 of 2020 on Administration and Criminal Trial in The Court Electronically provides 2 (two) alternatives to conduct trials in criminal cases, namely offline and online. This is not previously regulated in the Criminal Procedure Law (KUHAP) or other legal regulations. Second, with regard to the process of proving in criminal cases at online trials basically still follow the provisions in the criminal event law and have the same value or power of proof as trials conducted offline.